Evaluación fitoquímica y actividad biológica de Desmodium molliculum ( H.B.K.) D.C. ( Manayupa) - Lozano R., Nancy (2001)
There were threesamples of Desmodium molliculum (H.B.K.) D.C. (Manayupa), which were assessed from Jaen, Cajamarca (sample El), Huanuco (sample E2) and Huancayo, Junin (sample E3), caBed it too "Runa manayupana", which is used Iike diuretic, depurative, antihemorragic, antidisenteric, anti-inflammatory of urines tracts, liver and kidneys.The results of toxic's biotest in Artemia salina Leach showed a good biology activity with values LC50: 100,427 μ,g/mL (sample El), LC50: 101,5567 μ,g/mL, LC50: 122,17 μ,g/mL (sample E2) and LC50: 93,5111 ug/mL (sample E3).About of the phitochemistry study are observed whatthree samples in study, exhibit great quantity of secondary metabolits, are appreciated flavonoids in great quantity.About of the assesses in effect anti-inflarnmatory for peroral administration, the sample E3 showed greather activity than E2 and E1 (% efficience anti-inflammatory = 36,2) nether to activity of LA Dexametasone. While in one topic administration the extract El, showed greather anti-inflammatory activity (% efficience anti-inflammatory = 35,7).In account cicatrizant effect for peroral way, the extract E3 showed greather activity ( % efficience cicatrizant = 28,1), while for topic way on damages induced on the loin of mouse, El showed greather activity (% efficience cicatrizant = 31,6).The hematology study showed that the mononucleares elements were in a big amount, just to finished the evaluation subcronic anti-inflammatory treatment with E1.To concluded that the sample from Jaen (Cajamarca) have the best biology activity assesses.